2010
DOI: 10.1007/s11538-010-9514-7
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Hyperbaric Oxygen Therapy Applied to Chronic Diabetic Wounds

Abstract: The failure of certain wounds to heal (including diabetic foot ulcers) is a significant socioeconomic issue for countries worldwide. There is much debate about the best way to treat these wounds and one approach that is shrouded with controversy is hyperbaric oxygen therapy (HBOT), a technique that can reduce the risk of amputation in diabetic patients.In this paper, we develop a six species mathematical model of wound healing angiogenesis and use it to investigate the effectiveness of HBOT, compare the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 99 publications
0
26
0
1
Order By: Relevance
“…Usually, 10–30 treatments are performed. HBOT has turned out to be an effective tool to increase pO 2 values in wound tissue, and the effects of HBOT on chronic wound healing have been described by a mathematical model 108,109,111 . Sheikh et al.…”
Section: Therapeutic Wound Oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, 10–30 treatments are performed. HBOT has turned out to be an effective tool to increase pO 2 values in wound tissue, and the effects of HBOT on chronic wound healing have been described by a mathematical model 108,109,111 . Sheikh et al.…”
Section: Therapeutic Wound Oxygenationmentioning
confidence: 99%
“…HBOT has turned out to be an effective tool to increase pO 2 values in wound tissue, and the effects of HBOT on chronic wound healing have been described by a mathematical model. 108,109,111 Sheikh et al 112 demonstrated increased VEGF expression in rats treated with HBOT, and Hopf et al 30 showed a stimulation of neovascularization in hypoxic tissue after HBOT. Moreover, oxygen administration has been shown to increase VEGF mRNA levels in endothelial cells and macrophages and VEGF protein expression in wound fluids in vivo.…”
Section: Therapeutic Wound Oxygenationmentioning
confidence: 99%
“…However, the details of the models are diverse (Jin et al, 2016b;Simpson et al, 2011). The motility of cells can be modelled by: linear diffusion (Jackson et al, 2015;Maini et al, 2004;Sengers et al, 2007;Simpson et al, 2007;Swanson et al, 2003); nonlinear diffusion where the diffusivity increases with density (Bianchi et al, 2016;Flegg et al, 2009;Sengers et al, 2007), and nonlinear diffusion where the diffusivity decreases with density King and McCabe, 2003); nonlinear advection to describe directed motility, such as chemotaxis (Bianchi et al, 2016;Flegg et al, 2010), haptotaxis (Marchant et al, 2001), and cell-cell adhesion (Armstrong et al, 2009). Similarly, the proliferation of cells is often modelled using a logistic source term (Maini et al, 2004;Sengers et al, 2007;Simpson et al, 2007), but there are also many other options for modelling carrying capacity-limited proliferation (Browning et al, 2017;Gerlee, 2013;Tsoularis and Wallace, 2002).…”
Section: Continuum Models In Cell Biology Applicationsmentioning
confidence: 99%
“…Antihipoksični efekat HBOT se postiže povećanjem njegove rastvorljivosti u tjelesnim tečnostima, a vjerovatno se postižu i određeni efekti preko kiseonik -vezujućih proteina u različitim tkivima. Osim poboljšanja tkivne oksigenacije, efekti HBOT mogu da uključuju i stimulaciju angiogeneze, aktivaciju fibroblasta sa stvaranjam kolagena (profibrotički efekat), povećanu fagocitoznu aktivnost makrofaga, čime se poboljšava antimikrobna zaštita tkiva, smanjenje edema tkiva, prevenciju lipidne peroksidacije i dr. [5][6][7][8][9].…”
Section: Uvodunclassified